The Impact of Temporary Protected Status on Immigrants' Labor Market Outcomes - Orrenius, Pia M.; Zavodny, Madeline (American Economic Review, 2015)
The United States currently provides Temporary Protected Status (TPS) to more than 300,000 immigrants. TPS is typically granted if dangerous conditions prevail in migrants' home countries. Individuals with TPS are allowed to stay and work in the United States temporarily. Little is known about how TPS affects beneficiaries, most of whom are unauthorized prior to receiving TPS. Our results suggest that TPS eligibility leads to higher employment rates among women and higher earnings among men. The results have implications for recent programs that allow millions of unauthorized immigrants to receive temporary permission to remain and work in the United States.